1978
DOI: 10.1083/jcb.78.3.910
|View full text |Cite
|
Sign up to set email alerts
|

Histone localization in polytene chromosomes by immunofluorescence.

Abstract: Polytene chromosomes of Chironomus thurnmi were treated with antisera elicited by purified calf thymus histone fractions, and the location of each histone type was visualized by the indirect immunofluorescence technique. Each of the antisera produced specific and distinct patterns of fluorescence, suggesting that it is possible to use the indirect immunofluorescence technique to study the in situ organization of each histone in the various regions of the chromosomes. H1 and H2A antisera produced diffuse fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…4b). This result agrees with earlier studies (37) and is consistent with a uniform distribution of H2A-containing nucleosomes along the chromosome paralleling the density of DNA. The H2A result contrasts markedly with the complex immunofluorescence pattern observed for H2Av, which did not correlate with the banded structure of the chromosome (compare Figs.…”
Section: Distribution Of H2av In Polytenesupporting
confidence: 82%
“…4b). This result agrees with earlier studies (37) and is consistent with a uniform distribution of H2A-containing nucleosomes along the chromosome paralleling the density of DNA. The H2A result contrasts markedly with the complex immunofluorescence pattern observed for H2Av, which did not correlate with the banded structure of the chromosome (compare Figs.…”
Section: Distribution Of H2av In Polytenesupporting
confidence: 82%
“…7 A) while tagged histone H3-HA1 localized throughout the nucleus as expected for histone H3 (Fig. 7 D; Kurth et al, 1978). The chimeric CA/H3-HA1, possessing the unique NH2 terminus of CENP-A, failed to localize at centromeres but rather was distributed throughout the nucleus (Fig.…”
Section: The Histone Fold Domain Of Cenp-a Is Required For Centromerimentioning
confidence: 62%
“…In some cases the transcriptionally active loci can be detected as "puffs" by phase-contrast microsopy or, more reliable, by autoradiographic techniques using labeled uridine. Immunofluorescence studies with antihistone sera produce a distinct banding pattern reminiscent of that observed by phase-contrast microscopy (22) (Fig. 3).…”
Section: Transcriptionally Active Chromatinmentioning
confidence: 52%